Exploring the processes of cryomechanodestruction and mechanochemistry when devising nano-technologies for the frozen carotenoid plant supplements - Pavlyuk, Raisa; Pogarska, Viktoriya; Timofeyeva, Nadiya; Bilenko, Leonida; Stukonozhenko, Tetyana (Eastern-European Journal of Enterprise Technologies, 2016)
The influence of cryomechanodestruction is examined on the activation and destruction of heteropolysaccharides – protein nano complexes with carotene and other low-molecular BAS, such as L-ascorbic acid, phenolic compounds, which are in vegetable raw materials are in the non-active bound form, when developing the nanotechnologies of plant supplements, in particular, frozen nanopuree from carrot, sweet pepper, pumpkin, tomato, apricot, buckthorn. We discovered regularities and mechanisms of comprehensive effect of deep processing the carotene-containing vegetable raw materials, freezing and cryomechanodestruction for the preservation and extraction of carotenoids, bound in nano complexes with biopolymers, into free and hydrophilic forms. It was found that in the development of nanotechnologies for cryopuree, there occurs the extraction of b-carotene into free form, by 3...3.5 times larger than in the original raw materials. The benefits of the research include the fact that, as a result of using comprehensive effect of cryotreatment of raw materials and cryomechanodestruction, the nano complexes of biopolymers with low-molecular substances, such as β-carotene, L-ascorbic acid, low-molecular phenolic compounds, are destroyed and there occurs their transformation from hidden, bound form into the free soluble easily digestible form – the nanoform. This makes it possible to reveal the biopotential of plant cell, tissue more effectively and extract from them the hidden forms of biologically active substances with fundamentally new chemical composition and high consumer properties, which might be used when creating health improving food products.